Nyanga pottery and the Manyika ethnohistory: towards a decolonised archaeology of the Nyanga agricultural complex - Robert T. Nyamushosho; Njabulo Chipangura; Takudzwa B. Pasipanodya; Foreman Bandama; Shadreck Chirikure; Munyaradzi Manyanga (Heliyon, 2021)
Ancient pottery from the Nyanga agricultural complex (CE 1300–1900) in north-eastern Zimbabwe enjoys more than a century of archaeological research. Though several studies dedicated to the pottery have expanded the frontiers of knowledge about the peopling of Bantu-speaking agropastoral societies in this part of southern Africa, we know little about the social context in which the pottery was made, distributed, used, and discarded in everyday life. This mostly comes from the fact that the majority of the ceramic studies undertaken were rooted in Eurocentric typological approaches to material culture hence these processes were elided by most researchers. As part of the decolonial turn in African archaeology geared at rethinking our current understanding of the everyday life of precolonial agropastoral societies, we explored the lifecycle of traditional pottery among the Manyika, one of the local communities historically connected to the Nyanga archaeological landscape. The study proffered new dimensions to the previous typological analyses. It revealed a range of everyday roles and cultural contexts that probably shaped the lifecycle of local pottery in ancient Nyanga.